2020
DOI: 10.1111/are.14797
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of various crude feed ingredients to juvenile olive flounder (Paralichthys olivaceus, Temminck & Schlegel) and its application to aquaculture

Abstract: The olive flounder (Paralichthys olivaceus, Temminck & Schlegel) is the most popular and commercially important marine fish species in aquaculture in eastern Asian countries, such as Korea, China and Japan, because of its high market value and rapid growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The consistent result was also reported in rockfish (Kim et al, 2020; Kim & Cho, 2019). Jeong et al (2020) also revealed that inclusion of 50 g/kg JMM in EP effectively increased feed intake and eventually elevated weight gain, SGR, and CF of olive flounder. In fish, some AAs (alanine, arginine, betaine, glutamine, glycine, histidine, methionine, proline, and threonine) have been demonstrated as good feeding inducers or stimulants (Carr et al, 1996; Goh & Tamura, 1980; Ismail et al, 2020; Olsén & Lundh, 2016; Yacoob & Browman, 2007; Yeşilayer & Kaymak, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The consistent result was also reported in rockfish (Kim et al, 2020; Kim & Cho, 2019). Jeong et al (2020) also revealed that inclusion of 50 g/kg JMM in EP effectively increased feed intake and eventually elevated weight gain, SGR, and CF of olive flounder. In fish, some AAs (alanine, arginine, betaine, glutamine, glycine, histidine, methionine, proline, and threonine) have been demonstrated as good feeding inducers or stimulants (Carr et al, 1996; Goh & Tamura, 1980; Ismail et al, 2020; Olsén & Lundh, 2016; Yacoob & Browman, 2007; Yeşilayer & Kaymak, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Both rockfish (Kim et al, 2020) and olive flounder (Jeong et al, 2020) exhibited the strongest attractiveness to JMM among 15-16 common protein ingredients. Rockfish showed the strongest attractive behavior (movement of fish from acclimatization chamber toward the selected chamber after introduction of the experimental diets containing different levels of JMM) to the JMM 1000 diet, but the best growth in the JMM 400 diet in the current study, while diets containing 600, and 200 g/kg JMM exhibited the strongest attractive behavior in the same equipment used in the current study and achieved the best growth performance of olive flounder in the 8-week feeding experiment, respectively, in Jeong et al's (2022) study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anchovy meal (AM) and sardine meal (SM) are also supplemented in olive flounder diets as main protein sources (Back et al, 2020;Bae et al, 2020;Park et al, 2021). It was recently reported that jack mackerel meal (JMM) enhances feed consumption of olive flounder due to its high attractiveness (Jeong et al, 2020). Tuna meal (TM), pro-duced by tuna byproducts, is incorporated in commercial olive flounder feed to reduce production costs as reported by Kim et al (2014).…”
Section: Introductionmentioning
confidence: 99%